Service Deployment Algorithms for Vertical Search Engines - Marin-Caihuan, J; Inostrosa-Psijas, A (2013)
Web search engines are systems devised to cope with highly dynamic and demanding query rates. These systems are composed by several services, each one dedicated to execute a single operation required to solve a query. Services are allocated into thousand of multi-core processors organized in racks. Some services communicate more than others, so it is desirable to put them in the same rack. In this work, we present and evaluate deployment algorithms for a web search engine. In particular, we focus on vertical search engines with speciffic on-line content which may include shopping, advertisement, etc.. Our goal is to improve the performance of a search engine by reducing communication time. Communication among services is performed by means of a fast and complex network supporting parallel sending and receiving of messages. We propose a communication-graph-based method, in which processors are the nodes of the graph and communication between them is represented as weighted arcs. Results show that our proposal method is able to reduce maximum query response time. © 2013 IEEE.